Impaired sweating in patients with cholinergic urticaria is linked to low expression of acetylcholine receptor CHRM3 and acetylcholine esterase in sweat glands - Wang, Yiyu; Scheffel, Jörg; Vera, Carolina Ayala; Liu, Wei; Günzel, Dorothee; Terhorst-Molawi, Dorothea; Maurer, Marcus; Altrichter, Sabine (Frontiers in Immunology, 2022)
Introduction Cholinergic urticaria (CholU), a frequent form of chronic inducible urticaria, is characterized by itchy wheals and angioedema in response to sweating. As of now, the rate and pathophysiological relevance of impaired sweating, in patients with CholU, are ill defined. We aimed in assessing, in CholU patients, the rate and extent of impaired sweating and its links to clinical and pathophysiological features of CholU. Patients and Methods We assessed sweating in patients with CholU (n=13) subjected to pulse-controlled ergometry (PCE) provocation testing. Pre- and post-PCE biopsies of lesional (L) and non-lesional (NL) skin were analysed for the expression of the acetylcholine receptor CHRM3 and acetylcholine esterase (ACh-E) by quantitative histomorphometry and compared to those of healthy control subjects (HCs). CholU patients were assessed for disease duration and severity as well as other clinical features. Results Of 13 patients with CholU, 10 showed reduced sweating in response to PCE provocation, and 3 had severely reduced sweating. Reduced sweating was linked to long disease duration and high disease severity. CholU patients with impaired sweating responses showed reduced sweat gland epithelial expression of CHRM3 and ACh-E. Discussion Reduced sweating is common in CholU patients, especially in those with long standing and severe disease, and it can be severe. Reduced expression of CHRM3 and ACh-E may the cause or consequence of CholU, in patients with impaired sweating, and this should be explored by further studies.